A microsatellite repeat in PCA3 long non-coding RNA is associated with prostate cancer risk and aggressiveness. Issue 1 (December 2017) - Lai, John; Moya, Leire; An, Jiyuan; Hoffman, Andrea; Srinivasan, Srilakshmi; Panchadsaram, Janaththani; Walpole, Carina; Perry-Keene, Joanna; Chambers, Suzanne; Lehman, Melanie; Nelson, Colleen; Clements, Judith; et al.
Abstract Short tandem repeats (STRs) are repetitive sequences of a polymorphic stretch of two to six nucleotides. We hypothesized that STRs are associated with prostate cancer development and/or progression. We undertook RNA sequencing analysis of prostate tumors and adjacent non-malignant cells to identify polymorphic STRs that are readily expressed in these cells. Most of the expressed STRs in the clinical samples mapped to intronic and intergenic DNA. Our analysis indicated that three of these STRs (TAAA-ACTG2, TTTTG-TRIB1, and TG-PCA3 ) are polymorphic and differentially expressed in prostate tumors compared to adjacent non-malignant cells. TG-PCA3 STR expression was repressed by the anti-androgen drug enzalutamide in prostate cancer cells. Genetic analysis of prostate cancer patients and healthy controls (N > 2, 000) showed a significant association of the most common 11 repeat allele of TG-PCA3 STR with prostate cancer risk (OR = 1.49; 95% CI 1.11–1.99;P  = 0.008). A significant association was also observed with aggressive disease (OR = 2.00; 95% CI 1.06–3.76;P  = 0.031) and high mortality rates (HR = 3.0; 95% CI 1.03–8.77;P  = 0.045). We propose that TG-PCA3 STR has both diagnostic and prognostic potential for prostate cancer. We provided a proof of concept to be applied to other RNA sequencing datasets to identify disease-associated STRs for future clinical exploratory studies.